PEMANFAATAN PLATFORM CANVA DALAM PENGEMBANGAN E-MODUL INTERAKTIF: STRATEGI MODUL PEMBELAJARAN MODERN - Gholib Assalam; Joko Subando (INOVASI : Jurnal Ilmiah Pengembangan Pendidikan, 2025)
The advancement of digital technology has driven transformation in the field of education, including in the development of instructional media. One notable innovation is the utilization of graphic design platforms such as Canva for creating interactive e-modules. This study aims to explore the potential of Canva as a tool for designing engaging, responsive, and learner-oriented instructional modules. Using a literature review approach, this research analyzes various scholarly sources discussing the role of e-modules, interactivity in learning, and the effectiveness of Canva in supporting teaching and learning processes. The findings indicate that Canva offers advantages in terms of user-friendliness, design flexibility, and multimedia integration capabilities, which enhance student engagement and learning motivation. Canva-based e-module development also aligns with 21st-century learning demands that emphasize creativity, digital literacy, and independent learning. Therefore, Canva is a promising alternative strategy for developing contemporary learning modules, particularly in the era of digital education and the Merdeka Curriculum.